THE CITIZEN PARTICIPATION OF PEOPLE WITH DISABILITIES - Vidal-García, Josefa (2021)
Disability is the result of a disease, aggression, damage, or deterioration of health, which forces the individual to stay within a sphere of dependency, therefore in Spain this group has a low citizen participation, since citizen participation, is the intervention of citizens in the public sphere, fulfilling functions of social interests, with a community character that favour democracy and intervene in public decisions. Based on the aforementioned, the objective of this work is to systematically analyse the disability paradigm around citizen participation in Spain, therefore the recommendations were studied by the Committee of the Convention on the rights of people with disabilities, seeking to ensure the suffrage of all these people, independently or assisted by a person they trust, however the privileged scope of citizen participation in Spain is the local level, for which it has been define that disability is the result of a physical, social and attitudinal deficiency, which does not prevent their participation in the suffrage and citizen participation, to improve their quality of life.